2023
DOI: 10.1111/asj.13808
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for production, reproduction, and growth curve of Fars indigenous chicken

Abstract: Iranian native chicken, including Fars indigenous chicken, is an important genetic resource due to its adaptation to stressful environmental conditions, good endurance and resistance to disease. The aim of this research was to determine the genetic infrastructure of Fars indigenous chicken using several nonlinear functions. The dataset included body weight at hatch (BW1), body weight at the 8th week (BW8), body weight at the 12th week (BW12), weight at sexual maturity (WSM), age at sexual maturity (ASM), numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, Nguyen et al identified Gompertz as the best fitting model for body weight when exploring the optimal growth model for local chickens in Vietnam [30]. Neysi et al used eight models to fit the growth characteristics of Fars indigenous chickens, and ultimately determined that the Gompertz model is more suitable for describing its growth pattern [31]. Manjula et al found that the logistic model was more suitable for fitting the growth of Korean native chickens [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nguyen et al identified Gompertz as the best fitting model for body weight when exploring the optimal growth model for local chickens in Vietnam [30]. Neysi et al used eight models to fit the growth characteristics of Fars indigenous chickens, and ultimately determined that the Gompertz model is more suitable for describing its growth pattern [31]. Manjula et al found that the logistic model was more suitable for fitting the growth of Korean native chickens [32].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal environmental effects appear before and after laying, the later may be pre-hatching and post-hatching effects that affect egg quality traits and bird weight at hatching (Prado-Gonzalez et al, 2003). The importance of maternal effects on body weight in chickens has been shown in various ies (Maniatis et al, 2013;Neysi et al, 2023;Rahmanian et al, 2015). However, due to the difference in the genetic structure of different breeds and populations, different models have been selected as optimal models for the genetic evaluation of growth-related traits.…”
Section: Discussionmentioning
confidence: 99%